2011
DOI: 10.1016/j.molonc.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Knock‐down of SOX11 induces autotaxin‐dependent increase in proliferation in vitro and more aggressive tumors in vivo

Abstract: Proliferation Autotaxin NOD-SCID mice MCL Z138 A B S T R A C TThe transcription factor SOX11 is a novel diagnostic marker for mantle cell lymphoma (MCL), distinguishing this aggressive tumor from potential simulators. Recent data also show that the level of SOX11 correlates to in vitro growth properties in MCL, as well as the clinical progression. We have previously shown that MCL-associated pathways, such as Rb-E2F, are dysregulated leading to decreased proliferation upon overexpression of SOX11, emphasizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…Of interest, the Cyclin D1 related pathway Rb-E2F was shown to be affected by the increased level of SOX11 upon transient overexpression. 64 Biologically similar results were shown using a knock-down model where a number of genes, among others DBN1, previously associated with MCL and involved in migration, proliferation, and apoptosis was co-regulated with SOX11, 71 pinpointing the global impact of SOX11 on MCLassociated gene expression. In this stable knock-down model, it was further shown that SOX11 reduction caused increased growth, partially driven by the upregulation of autotaxin (ATX).…”
Section: The Molecular Function Of Sox11 In MCLsupporting
confidence: 57%
See 2 more Smart Citations
“…Of interest, the Cyclin D1 related pathway Rb-E2F was shown to be affected by the increased level of SOX11 upon transient overexpression. 64 Biologically similar results were shown using a knock-down model where a number of genes, among others DBN1, previously associated with MCL and involved in migration, proliferation, and apoptosis was co-regulated with SOX11, 71 pinpointing the global impact of SOX11 on MCLassociated gene expression. In this stable knock-down model, it was further shown that SOX11 reduction caused increased growth, partially driven by the upregulation of autotaxin (ATX).…”
Section: The Molecular Function Of Sox11 In MCLsupporting
confidence: 57%
“…In this stable knock-down model, it was further shown that SOX11 reduction caused increased growth, partially driven by the upregulation of autotaxin (ATX). 71 Of interest, ATX has previously has been reported to be involved in tumor aggressiveness and angiogenesis. 72 Besides GEP, chromatin immunoprecipitation (ChIP) has been used alone, or in combination with GEP to assess the transcription factor binding sites of SOX11.…”
Section: The Molecular Function Of Sox11 In MCLmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of two decades of research, a large number of studies have established that in addition to cellautonomous cancer hallmarks such as differentiation ( 58,(103)(104)(105)(106), survival (107)(108)(109)(110)(111)(112), proliferation ( 58,(113)(114)(115)(116), and migration/metastatic behavior ( 50, 74,92,[117][118][119][120][121][122], the aberrant expression/amplifi cation of ATX activity can also dysregulate multiple cancer pathobiology systemic hallmarks including angiogenesis ( 119,123 ), metabolic homeostasis ( 56-59, 104, 124, 125 ), and immune system function ( 126 ).…”
Section: Role In Physiology and Cancer Pathophysiologymentioning
confidence: 99%
“…Finally, we have recently published data, demonstrating a growth regulatory role for SOX11 in in-vitro models of MCL [18] and EOC [8], which was further confirmed using xenotransplants in mice [19]. Together these data suggest a key growth regulatory role of SOX11 in these neoplasms and emphasize the need for functional antibodies for experimental use in various technologies, including imaging and flow cytometry applications.…”
Section: Introductionmentioning
confidence: 59%